2019
DOI: 10.7150/thno.37717
|View full text |Cite
|
Sign up to set email alerts
|

HBX-induced miR-5188 impairs FOXO1 to stimulate β-catenin nuclear translocation and promotes tumor stemness in hepatocellular carcinoma

Abstract: Cancer stem cells (CSCs) are the key factor in determining cancer recurrence, metastasis, chemoresistance and patient prognosis in hepatocellular carcinoma (HCC). The role of miR-5188 in cancer stemness has never been documented. In this study, we investigated the clinical and biological roles of miR-5188 in HCC. Methods: MiRNA expression in HCC was analyzed by bioinformatics analysis and in situ hybridization. The biological effect of miR-5188 was demonstrated in both in vitro and in vivo studies through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 40 publications
5
56
0
Order By: Relevance
“…The immunohistochemical staining intensity was evaluated as described previously. 50 A score >6 was classified as high expression, and a score ≤6 was classified as low expression.…”
Section: Ihcmentioning
confidence: 99%
“…The immunohistochemical staining intensity was evaluated as described previously. 50 A score >6 was classified as high expression, and a score ≤6 was classified as low expression.…”
Section: Ihcmentioning
confidence: 99%
“…[12][13][14] Recent studies suggested the powerful function of miR-5188 in cancer progression. 15,16 However, the biological effects of miR-5188 in glioma remain insufficiently understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that gene expression of β-catenin targets, including glutamine synthetase, GPR49, Slc1a2, and TCF, was upregulated in tumors ( Figure 2C). Expression of FoxO1, which is known to suppress β-catenin activity (27), was significantly reduced in both tumor and non-tumor tissues ( Figure 2C). We also found that protein expression of glutamine synthetase was highly upregulated in tumor tissue compared to other tissues (Figure 2A, D).…”
Section: β-Catenin Activation In Car/atx Tumorsmentioning
confidence: 99%